Developmentally regulated expression of the BRI1 brassinosteroid receptor in Arabidopsis thaliana - Hategan Lidia; Bindics János; Szekeres Miklós; Hungarian Congress on Plant Biology, 9., 2008, Szeged (2008)
Brassinosteroids (BRs) are important regulators of morphogenic events during plant development. The lack of active transport and well-characterized biosynthesis offer ideal conditions for studying the local and temporal effects of this hormone group. While recent studies have found clear coincidence between the sites of BR accumulation and organ differentiation, they have also provided evidence for developmental changes in hormone susceptibility. In order to investigate the role of the BR receptor BRI1 in the modulation of hormone sensitivity, we studied the time course and localization of BRI1 gene activity in Arabidopsis seedlings. To this end, we generated transgenic lines carrying BRI1 promoter-driven luciferase or GUS reporter genes and characterized the expression patterns of these chimeric genes. Our results showed increased BRI1 expression in dark grown seedlings, particularly in the elongation zone of the hypocotyl, and also at the sites of organ development in green seedlings. These data indicate that, in addition to local increases in the hormone level, the abundance of the receptor can also be instrumental in eliciting the BR response.